Discussion on "Sequential detection/isolation of abrupt changes" by Igor V. Nikiforov. Issue 3 (2nd July 2016) - Baron, Michael; Zacks, Shelemyahu
ABSTRACT: Professor Nikiforov gave an excellent introduction to the modern theory and applications of detection/isolation. We discuss possible consequences of the "ultra-minimax" (working against the worst-worst-worst case) approach as well as some extensions and modifications of the problem.